1998
DOI: 10.1021/bi9721086
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of the Removal of Evolutionary Conserved Disulfide Bridges on the Structure and Function of Charybdotoxin and Evidence That Particular Cysteine Spacings Govern Specific Disulfide Bond Formation

Abstract: Scorpion toxins are miniglobular proteins containing a common structural motif formed by an alpha-helix on one face, an antiparallel beta-sheet on the opposite face, and three disulfide bonds making up most of its internal volume. We have investigated the role of these evolutionary conserved bonds by replacing each couple of bridged cysteine residues of the scorpion charybdotoxin by a pair of nonbridging L-alpha-aminobutyric acid (Aba) residues. Three analogues were obtained by solid-phase synthesis, Chab I, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 65 publications
3
33
1
Order By: Relevance
“…The Cys in the R⅐F/-⅐G⅐K⅐C sequence forms a disulfide bridge that stabilizes scorpion toxin structure, thereby positioning Arg and Lys to interact with BK. Mutating that Cys dramatically reduced CTx affinity for BK (19). We found that mASIC1a-C194A still inhibited BK current and pH 6 solution relieved inhibition (Fig.…”
Section: Asic1amentioning
confidence: 68%
See 1 more Smart Citation
“…The Cys in the R⅐F/-⅐G⅐K⅐C sequence forms a disulfide bridge that stabilizes scorpion toxin structure, thereby positioning Arg and Lys to interact with BK. Mutating that Cys dramatically reduced CTx affinity for BK (19). We found that mASIC1a-C194A still inhibited BK current and pH 6 solution relieved inhibition (Fig.…”
Section: Asic1amentioning
confidence: 68%
“…1A) (17). In ␣-KTx toxins, the Lys side chain plugs the channel pore, the Arg interacts with residues in the outer vestibule of K ϩ channels, and the Cys forms a disulfide bond that stabilizes toxin structure (17)(18)(19). Although it seemed clear that the ASIC extracellular domain did not resemble an ␣-KTx toxin, the conserved sequence led us to hypothesize that ASICs might interact with and inhibit K ϩ channels.…”
mentioning
confidence: 99%
“…The analogs were fully active in vitro on ion channels and in vivo when tested for neurotoxicity in mice [20]. Similarly, charybdotoxin (ChTx) analogs, lacking the first disulfide bridge, preserve the ability to form native disulfide pairings, in contrast to analogs lacking the second or third bridge [21]. On the other hand, studies on mono-loop analogues of iberiotoxin (IbTx) indicated that no single loop derivative displayed biological activity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of this critical disulfide bridge significantly disrupted the ordered secondary structure and increased the proinsulin's susceptibility to proteolysis [119]. At the other extreme of the spectrum, multiple disulfide bridges have occasionally been noted to be redundant, with folding and structural stability maintained with a reduced number of native disulfide bridges [121,122].…”
Section: Oxidation-reductionmentioning
confidence: 99%
“…In the case of GI a-conotoxin, Zhang and Snyder [128] demonstrated that the propensity of the peptide toxin to fold into the native globular conformation is largely dependent on the loop sizes of the two intercysteine loops. Similarly, the disulfide connectivity of charybdotoxin from the venom of the scorpion, Leiurus quinquestriatus, was influenced by the position of the cysteine residues and intercysteine loop spaces [122]. In an engineered barnase structure, the inclusion of disulfide bridges reduced the rate of protein unfolding [129].…”
Section: Oxidation-reductionmentioning
confidence: 99%